Menjadi Pemimpin Yang Efektif dan Berpengaruh di Madrasah - Munganatul Khoeriyah (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2020)
The study to aim provides an overview of being effective and influential leader. This type of research is library research. This reaserch using books, article leadership looking for scientific facts, then analyzed by analisis description method. This research result reveal that instrumen efective and influential leader is impermanent. Leaedership style is determine influnce that he leads. Build the trust of school residents and the community through of leadership style is the key open the way succsess. Strong leader and management are needed for the succsess of the institution. Ulil albab is nickname for profiles of succsesfull leadership in madrasah.